Analysis of Glyphosate Herbicide Residues in Coffee Plantations in Bener Meriah Regency - Suheri, Dedi; Nasruddin, Nasruddin; Ismadi, Ismadi; Jamidi, Jamidi; Baidhawi, Baidhawi (International Journal of Engineering, Science and Information Technology, 2025)
Coffee is a leading plantation commodity as it serves as a source of income for farmers, provides raw materials for industries, creates job opportunities, and promotes regional development in Bener Meriah Regency. To achieve optimal production results, farmers must adequately manage and maintain their coffee plantations, one way being the reduction of chemical usage that may affect the coffee beans. The negative impact of excessive chemical use includes rejecting exports to several European countries due to residue levels exceeding the limits set by European Union regulations. Therefore, analyzing herbicide residues and studying the factors affecting their persistence is necessary. Sampling was conducted in five sub-districts: Gajah Putih, Bandar, Permata, Timang Gajah, and Bukit, by collecting soil and bean samples from five points in each sub-district for analysis using gas chromatography. The research showed glyphosate residue levels of 0.002 mg/kg in each soil and bean sample. These levels are considered low compared to the maximum residue limit (MRL) for coffee, which is 0.1 mg/kg. This indicates that glyphosate residue contamination in the sampled plots is considered safe for consumption. Observations and interviews with farmers concluded that the low residue levels in the soil samples were influenced by several factors, including climate (temperature, humidity, rainfall), soil characteristics, topography, herbicide characteristics, and weed types.